Atezolizumab Monotherapy or Plus Chemotherapy in First-Line Treatment for Advanced Non-Small Cell Lung Cancer Patients: A Meta-Analysis - Li, Dan-Ni; Lu, Wen-Qing; Yang, Bo-Wen; Zhang, Ling-Yun; Jin, Bo; Wang, Shuo; Che, Xiao-Fang; Li, Ce; Liu, Yun-Peng; Qu, Xiu-Juan (Frontiers in Immunology, 2021)
Background: Atezolizumab plus chemotherapy has been recommended as first-line treatment option for patients with advanced non-small cell lung carcinoma (NSCLC) irrespective of programmed cell death-ligand 1 (PD-L1) expression. Until now, little is known about the efficacy and treatment related adverse effects (TRAEs) of subtracting chemotherapy from the combination for patients with high PD-L1 expression. Thus, we performed an indirect comparison between atezolizumab plus chemotherapy and atezolizumab. Methods: A total of five eligible randomized controlled trials (RCTs) were identified from PubMed, EMBASE, and Cochrane Central controlled trial registries, using keywords including atezolizumab, PD-1, PD-L1, NSCLC and RCT. The clinical outcomes of objective response rate (ORR), progression-free survival (PFS), OS and TRAEs were extracted and evaluated. Using the indirect analysis, the efficacy and TRAEs were compared between arm A (atezolizumab plus chemotherapy) and arm C (atezolizumab), linked by arm B (chemotherapy). Results: Direct comparison revealed that both atezolizumab plus chemotherapy (HR 0.65, P = 0.003) and atezolizumab alone (HR 0.59, P = 0.010) significantly improved OS compared with chemotherapy. More importantly, the indirect comparison showed that atezolizumab plus chemotherapy was not superior to atezolizumab regarding OS (RR 1.10, P =0.695) and ORR (RR 1.11, P = 0.645). However, patients who received atezolizumab combined chemotherapy experienced more ≥ grade 3 TRAEs (RR 4.23, P＜0.001) and TRAEs leading to drug discontinuation (RR 3.60, P＜0.001) than those treated with atezolizumab monotherapy. Conclusions：Atezolizumab monotherapy might be a better treatment option for patients with advanced NSCLC and high PD-L1 expression than atezolizumab plus chemotherapy.